Pengaruh Perputaran Kas Dan Perputaran Persediaan Terhadap Profitabilitas Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bei Periode 2019-2021 - Salwa Salsabila; Diah Yudhawati; Titing Suharti (Universitas Veteran Bangun Nusantara, 2022)
In general, every company has the same goal, especially to generate profits and maintain the sustainability of the company in the future. One way to see a company's ability to generate profits is to analyze the company's profitability ratios, high profitability is able to support operational activities optimally. This study aims to determine the effect of cash turnover, inventory turnover on profitability in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The type of data in this research is quantitative data. Source of data is secondary data. The population in this study were pharmaceutical sub-sector companies listed on the IDX for the period 2019 to 2021 and the sampling used the purposive sampling method so that 5 companies were obtained as samples. Data analysis used in this research is descriptive analysis method, panel data regression test, classical assumption test, multiple linear regression test, hypothesis test and test of the coefficient of determination (R2) using Eviews version 12. The results of this study indicate that cash turnover is partially does not have a significant effect on profitability, inventory turnover partially has a significant effect on profitability, cash turnover and inventory turnover simultaneously have a significant effect on profitability.